A Panel Causality Analysis of the Relationship among Research and Development, Innovation, and Economic Growth in High-Income OECD Countries - (:unkn) unknown (Springer International Publishing, 2012)
This study examines possible causal relations among research and development (R&D) expenditures, innovation and economic growth in high income OECD countries. We test for both pairwise and multivariate causal relations by estimating a trivariate panel vector autoregressive (VAR) model through the GMM and panel fixed effects methods. Our bivariate panel causality test results suggest that R&D expenditures Granger cause innovation measured as the number of triadic patents; while technological innovations Granger cause economic growth, as presumed by endogenous growth theory. A reverse causality relation does also exist between economic growth and innovation, that is, the rate of growth of output accelerates the rate of technological change. Our multivariate causality tests further reveal that the market size and the rate of innovation together Granger cause R&D activity; while an increase in national output and R&D intensity jointly Granger-cause technological change. These findings suggest that both the “technology-push” and “demand-pull” models of innovation equally make sense. © 2012, Eurasia Business and Economics Society.
Keywords: Economic Growth; Panel Granger-Causality; Patents; Research and Development; Technological Change